Exploring the Grammatical Structure in the Short Story خبز الصغار based on Fillmore's Perspective - Ihsan Rahman; Moch Said (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The purposeof this study is to reveal the sentence structure in the short story خبزالصغار  based onCharles J. Fillmore's case grammar perspective. This study is adescriptive qualitative study. The data collection techniques consisted of three types oftechniques, namely reading, translating, and recording. The collected data was thenanalyzed using the distributional method with the basic technique ofsegmenting immediate constituents, which isa method of determining identity using a determinant tool in alanguage unit that divides a construction into the immediate constituents thatform it. The results of this study indicate that the sentence structure in the short storyخبز الصغار   consists of: (1) four modalities, namely intentional, epistemic, deontic, and dynamic;and (2) ten propositions, namely: agentive case (A), experiential case (P),instrumental case (I), objective case (O), source case (S), purpose case (T),locative case (L), temporal case (W), adjunct case (PNY), and benefactive case(B).